Current exercise-based rehabilitation impacts on poststroke exercise capacity, blood pressure, and lipid control: a meta-analysis - Moneruzzaman, Md.; Tang, Zhiqing; Li, Xiaohe; Sun, Weizhen; Maduray, Kellina; Luo, Meiling; Kader, Manzur; Wang, Yonghui; Zhang, Hao (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesThis systematic review aimed to evaluate the impact of post-stroke exercise-based rehabilitation programs on blood pressure, lipid profile, and exercise capacity.MethodsThrough a systemic search of literature from inception to 2024 using five databases, we analyzed data on the mean difference (MD) using a meta-analysis method to estimate effectiveness.ResultsThirty-seven randomized control trials were included encompassing various exercises such as aerobic, resistance, stretching, exergaming, robot-assisted training, and community-based training. Significant improvement was illustrated at discharge in systolic [MD 2.76 mmHg; 95% confidence interval (CI) −1.58 to 3.92, P < 0.05] and diastolic (MD 1.28 mmHg; 95% CI 0.54–2.12, P < 0.05) blood pressure and peak oxygen volume (MD −0.29 ml/kg/min; 95% CI −0.53 to 0.05, P < 0.05). We also observed significant improvement at discharge in high-density lipoprotein only after resistance exercise from two articles and low-density lipoprotein only in the intervention groups compared to the control groups from ten articles.ConclusionOverall, current exercise-based rehabilitation programs significantly improve blood pressure and exercise capacity in patients with stroke at discharge. However, lipoprotein changes remained inconclusive. Although ameliorative changes were noted in most variables, more research is needed to determine optimum exercise intensity, type combination, and health education to reduce post-stroke complications and mortality.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/X89FW.